Patterning Liquid Crystalline Organic Semiconductors via Inkjet Printing for High‐Performance Transistor Arrays and Circuits. (19th March 2021) - Fang, Xiaochen; Shi, Jialin; Zhang, Xiujuan; Ren, Xiaobin; Lu, Bei; Deng, Wei; Jie, Jiansheng; Zhang, Xiaohong
Abstract: Liquid crystalline (LC) organic semiconductors having long‐range‐ordered LC phases hold great application potential in organic field‐effect transistors (OFETs). However, to meet real device application requirements, it is a prerequisite to precisely pattern the LC film at desired positions. Here, a facile method that combines the technique of inkjet printing and melt processing to fabricate patterned LC film for achieving high‐performance organic integrated circuits is demonstrated. Inkjet printing controls the deposition locations of the LC materials, while the melt processing implements phase transition of the LC materials to form high‐quality LC films with large grain sizes. This approach enables to achieve patterned growth of high‐quality 2, 7‐dioctyl[1]‐benzothieno[3, 2‐b][1]benzothiophene (C8 ‐BTBT) LC films. The patterned C8 ‐BTBT LC film‐based 7 × 7 OFET array has 100% die yield and shows high average mobility of 6.31 cm 2 V −1 s −1, along with maximum mobility up to 9.33 cm 2 V −1 s −1 . As a result, the inverters based on the patterned LC films reach a high gain up to 23.75 as well as an ultrahigh noise margin over 81.3%. Given the good generality of the patterning process and the high quality of the resulting films, the proposed method paves the way for high‐performance organic integrated devices. Abstract : A new method of inkjet printing‐assisted melt processing is proposed for patterned growth of liquid crystalline thin films for high‐performance organic field‐effect transistor (OFET) arrays and integrated circuits. The OFET arrays exhibit uniform electrical properties with high average mobility of 6.31 cm 2 V −1 s −1 . Further, inverter circuits with high gain and large static noise margins of 81.3% are achieved.